2004
DOI: 10.1016/j.cub.2004.09.077
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin-1 Mediates Tubular Endosome-to-TGN Transport through Coincidence Sensing of High- Curvature Membranes and 3-Phosphoinositides

Abstract: We conclude that through coincidence detection SNX1 associates with a microdomain of the early endosome-characterized by high membrane curvature and the presence of 3-phosphoinositides-from where it regulates tubular-based endosome-to-TGN retrieval of the CI-MPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
573
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(613 citation statements)
references
References 37 publications
36
573
3
1
Order By: Relevance
“…One should be cautious to interpret data of knockdown and overexpression experiments because they often contradict. It was shown by siRNA that knockdown of SNX1 showed no effect on EGF receptor degradation (Gullapalli et al, 2004;Carlton et al, 2004) or on transferrin receptor trafficking (Carlton et al, 2004), whereas SNX1 is required for proper endosome retrieval of the CI-MPR (Carlton et al, 2005). This contrasts with the findings of previous studies using overexpression showing that overexpression of SNX1 enhances EGF receptor degradation (Kurten et al, 1996;Chin et al, 2001;Zheng et al, 2001), whereas other groups were unable to demonstrate that overexpression of SNX1 or SNX2, 3, or 4 increases the turnover of insulin or EGF receptors (Haft et al, 1998).…”
Section: Ehrab7a Overexpression Caused a Decrease Of Cp Activity Whimentioning
confidence: 67%
“…One should be cautious to interpret data of knockdown and overexpression experiments because they often contradict. It was shown by siRNA that knockdown of SNX1 showed no effect on EGF receptor degradation (Gullapalli et al, 2004;Carlton et al, 2004) or on transferrin receptor trafficking (Carlton et al, 2004), whereas SNX1 is required for proper endosome retrieval of the CI-MPR (Carlton et al, 2005). This contrasts with the findings of previous studies using overexpression showing that overexpression of SNX1 enhances EGF receptor degradation (Kurten et al, 1996;Chin et al, 2001;Zheng et al, 2001), whereas other groups were unable to demonstrate that overexpression of SNX1 or SNX2, 3, or 4 increases the turnover of insulin or EGF receptors (Haft et al, 1998).…”
Section: Ehrab7a Overexpression Caused a Decrease Of Cp Activity Whimentioning
confidence: 67%
“…In contrast, TfR-cluster were negative for SNX15 (Figure 18a, b), which was previously implicated in earlier sorting events such as the progression of CCVs to PI(3)P-enriched early endosomes (Danson, Brown et al 2013). Many SNXs contain BAR domains with membrane deforming activities (Carlton, Bujny et al 2004), some of which we found enriched on TfR-containing endosomes upon MTM1 depletion. Accordingly, we frequently observed strong tubulation of the endosomal recycling compartment in MTM1 knockdown cells (Figure 18c).…”
Section: Sub-plasma Membrane Early and Recycling Endosomes Accumulatementioning
confidence: 69%
“…Asn-Pro-x-Tyr (NPxY) motifs or PDZ (post synaptic density) -ligands, within the cytoplasmic domain of cargo proteins. Although SNX-BAR proteins can stabilize and drive tubule formation in vitro (Carlton, Bujny et al 2004), it remains unclear if SNX-BAR proteins are targeted to preexisting, tubular, PI-enriched endosomal subdomains or remodel the endosomal membrane themselves.…”
Section: Endosomal Sorting Occurs Via Tubular Cargo-enriched Subdomainsmentioning
confidence: 99%
“…Canonical BAR domains including ASAP1 BAR consist of three long, kinked ␣-helices that are bundled to form crescent-shaped homodimers . Several BAR domains found in amphipysin, endophilin, sorting nexins and Arf GAPs such as ACAP1 and ASAP1 sense or induce membrane curvature (Takei et al, 1999;Carlton et al, 2004;Peter et al, 2004;Masuda et al, 2006;Nie et al, 2006). Other BAR proteins, arfaptin 2 and APPL1, interact with small G proteins (Tarricone et al, 2001;Miaczynska et al, 2004).…”
Section: Discussionmentioning
confidence: 99%